2012
DOI: 10.1038/nature11428
|View full text |Cite
|
Sign up to set email alerts
|

A FOXO3–IRF7 gene regulatory circuit limits inflammatory sequelae of antiviral responses

Abstract: Antiviral responses must be tightly regulated to rapidly defend against infection while minimizing inflammatory damage. Type 1 interferons (IFN-I) are crucial mediators of antiviral responses1 and their transcription is regulated by a variety of transcription factors2; principal amongst these is the family of interferon regulatory factors (IRFs)3. The IRF gene regulatory networks are complex and contain multiple feedback loops. The tools of systems biology are well suited to elucidate the complex interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 33 publications
7
121
0
Order By: Relevance
“…Moreover, FOXO3 negatively regulates NF-kB activation (23), and FOXO3 is controlled by IKK-ε for regulating IFN-b expression (25). Intriguingly, FOXO3 has also been identified as a negative regulator of IRF7 transcription to participate in the antiviral response (26). Therefore, the function of FOXO3 in negatively regulating innate immunity response is well recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FOXO3 negatively regulates NF-kB activation (23), and FOXO3 is controlled by IKK-ε for regulating IFN-b expression (25). Intriguingly, FOXO3 has also been identified as a negative regulator of IRF7 transcription to participate in the antiviral response (26). Therefore, the function of FOXO3 in negatively regulating innate immunity response is well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, FOXO3 functions as a suppressor of NF-kB activation (23); on the other hand, IKK-a and IKK-b, two important kinases involved in NF-kB activation, phosphorylate and inactivate FOXO3 upon TNF-a stimulation (24). Recently, FOXO3 was reported to regulate IFN-b expression in an IKK-ε-controlled manner (25); additionally, the FOXO3-IRF7 gene regulatory circuit was also found to be crucial in antiviral response (26). However, the physiological role and the underlying mechanisms of FOXO3 in immunity are still poorly understood.…”
Section: F Orkhead Box O (Foxo) Transcription Factors Homologsmentioning
confidence: 99%
“…2/2 BMDMs, spontaneous basal ISG expression is also observed in macrophages deficient in other important IFN regulators, including TREX1, SAMHD1, and the transcriptional repressor FOXO3 (52)(53)(54)(55). Considering the potential detrimental effects of excessive IFN-b to the host, its production is tightly controlled, including on the transcriptional level.…”
Section: Isgs Similar To Atf3mentioning
confidence: 99%
“…Recently, Subramanian et al (2015) summarized the potential of data integration and network analysis for uncovering physiological processes of immune cells. For instance, in macrophages, gene expression dynamics and scanning for TF-binding sequence motifs have been used to elucidate transcriptional networks on a large scale (Ramsey et al, 2008;Litvak et al, 2012), while a combination of genome-wide mRNA expression data and network perturbation using methods such as RNAi knockdown was applied to identify useful intervention strategies in infections (König et al, 2010). In T helper (Th) cells, Ciofani et al (2012) demonstrated the power of data integration to construct a regulatory network for Th17 cell differentiation: they applied an integrative approach to delineate the Th17 cell global transcriptional regulatory network using meta-analysis of genome occupancy of multiple TFs, RNA-seq data of TF-deficient T cells, and immune cell transcriptome data.…”
Section: Introductionmentioning
confidence: 99%